2021
DOI: 10.3390/bios11090320
|View full text |Cite
|
Sign up to set email alerts
|

A Variable Height Microfluidic Device for Multiplexed Immunoassay Analysis of Traumatic Brain Injury Biomarkers

Abstract: Traumatic brain injury (TBI) is a leading cause of global morbidity and mortality, partially due to the lack of sensitive diagnostic methods and efficacious therapies. Panels of protein biomarkers have been proposed as a way of diagnosing and monitoring TBI. To measure multiple TBI biomarkers simultaneously, we present a variable height microfluidic device consisting of a single channel that varies in height between the inlet and outlet and can passively multiplex bead-based immunoassays by trapping assay bead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…g-EBL enables a high degree of control over channel topography down to the sub-micron regime and allows for the facile integration of numerous 3D profiles with different height profiles. This is in contrast to nonlithographical techniques, such as HF-dipping, which also allow for the fabrication of wedge-shaped profiles in fluidic devices for similar applications. , Additionally, the referenced devices require active pumping, significantly larger sample volumes, do not achieve sub-micron channel heights, and have very limited design flexibility. Our g-EBL high-resolution structure is subsequently replica-molded to obtain numerous negative daughter stamps (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…g-EBL enables a high degree of control over channel topography down to the sub-micron regime and allows for the facile integration of numerous 3D profiles with different height profiles. This is in contrast to nonlithographical techniques, such as HF-dipping, which also allow for the fabrication of wedge-shaped profiles in fluidic devices for similar applications. , Additionally, the referenced devices require active pumping, significantly larger sample volumes, do not achieve sub-micron channel heights, and have very limited design flexibility. Our g-EBL high-resolution structure is subsequently replica-molded to obtain numerous negative daughter stamps (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Clinically, protein biomarkers have been measured in CSF, serum, and plasma. Abbott is working on a test to measure biomarkers in whole blood, and Krausz et al demonstrated proof-of-concept GFAP measurements using spiked whole blood from a single donor [46,119]. Rickard et al demonstrated NAA measurements using fingerstick blood samples, but to the best of our knowledge, no one in industry has measured TBI protein biomarkers in a fingerstick blood sample, even though this sample is ideal for point-of-care biomarker measurements [48].…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…A summary of the assay characteristics for each early-stage sensor can be found in Table 2. [46] Notes: a LLODs were listed as ranges and were not separated by measurement technique, sample matrix, or biomarker. b LLODs and ranges were taken as the cutoff concentrations for each logic condition assignment.…”
Section: Early-stage Measurement Methods For Detection Of Tbi Protein Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations